(untitled) (Biological Sciences - PJSIR, 2006)
. Electrical conductances of some ammonium and tetraalkylammonium halides have been measured in differ- ent mass (20-80%) of 1,4-dioxane + water mixtures at 298.15 K. The limiting molar conductivity (L0), the association constant (KA), and association distance (R) in the solvent mixtures have been evaluated using Fuoss conductance equation (Fuoss, 1978). Based on the composition dependence of Walden product (L0h0), the influence of the mixed solvent composition on the solvation of ions has been also discussed. The results have been considered in terms of ion- solvent and ion-ion interactions and the structural changes in the mixed solvent systems